2018
DOI: 10.1038/s41467-018-04004-2
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear receptor NR2F6 inhibition potentiates responses to PD-L1/PD-1 cancer immune checkpoint blockade

Abstract: Analyzing mouse tumor models in vivo, human T cells ex vivo, and human lung cancer samples, we provide direct evidence that NR2F6 acts as an immune checkpoint. Genetic ablation of Nr2f6, particularly in combination with established cancer immune checkpoint blockade, efficiently delays tumor progression and improves survival in experimental mouse models. The target genes deregulated in intratumoral T lymphocytes upon genetic ablation of Nr2f6 alone or together with PD-L1 blockade reveal multiple advantageous tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(101 citation statements)
references
References 49 publications
2
99
0
Order By: Relevance
“…These prior researches implied that NR2F6 might be closely involved in the pathophysiology of malignant diseases and may play a dual role in cancer progression. Our present results are in line with previous studies, which indicate that NR2F6 expression promotes the CSC phenotype and induces cisplatin resistance of ovarian cancer cells by positively regulating transcriptional activation of the Notch3 signaling pathway.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These prior researches implied that NR2F6 might be closely involved in the pathophysiology of malignant diseases and may play a dual role in cancer progression. Our present results are in line with previous studies, which indicate that NR2F6 expression promotes the CSC phenotype and induces cisplatin resistance of ovarian cancer cells by positively regulating transcriptional activation of the Notch3 signaling pathway.…”
Section: Discussionsupporting
confidence: 93%
“…24 Previous studies have suggested that NR2F6 may function to positively regulate tumor cell survivability and to induce cancer progression. On the contrary, some reports have demonstrated that NR2F6 can act as a strong negative regulator for the function of the thyroid hormone (T3) nuclear receptor (TR), which regulates cell growth, differentiation and development 25 Notably, Victoria et al 9 reported that NR2F6 serves as safeguard to protect gut barrier homeostasis. Our knowledge of the maintenance of intestinal barrier homeostasis is dependent on the differentiation and maturation of stem cells from the intestinal recess.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this observation, NR2F6 has been documented to function as a gatekeeper of anti-tumor immunity through transcriptional repression of proinflammatory cytokines including IL-2, IFNγ, and TNFα (35,53). Furthermore, NR2F6 inhibition has been shown to augment the efficacy of ICB in preclinical prostate, melanoma, and colorectal cancer models, as well as increase tumor infiltration by IFNγ-positive T cells (35,54). However, an immunoevasive function for NR2F6 cancer-specific expression has not yet been described.…”
Section: Discussionmentioning
confidence: 69%
“…Our group identified the orphan nuclear receptor NR2F6 (nuclear receptor subfamily 2, group F, member 6; alias Ear2 and COUP-TFIII) as an intracellular immune checkpoint candidate fine-tuning adaptive immunity [25][26][27][28][29][30]. Nr2f6-deficient mice show an increased tendency for experimentally-induced neuroinflammation [25,26] as well as improved intratumoral effector T-cell response resulting in strongly decelerated tumor growth in different spontaneous as well as transplantable mouse tumor models [29,30]. Mechanistically, lymphatic NR2F6 acts as a negative-regulatory signaling intermediate downstream of the antigen receptor and sets the threshold of TCR/CD28 activation-induced effector functions by acting as a transcriptional repressor that directly antagonizes the DNA accessibility of activationinduced NFAT/AP-1 transcription factors at cytokine gene loci such as Il2 and Ifng [29,30].…”
Section: Introductionmentioning
confidence: 99%